An Analysis of Factors Causing Students’ Reticence in Speaking Classes - Artarini, Ni Putu Sita; Amin, Muhammad; Lestari, Yuni Budi; Junaidi, Ahmad (Jurnal Ilmiah Profesi Pendidikan, 2024)
This research describes factors causing many students in an EFL classroom struggle with speaking due to reticence, which significantly impacts their language learning and academic achievement. This study aims to identify and describe the factors causing students' reticence and propose possible strategies to cope with students' reticence in speaking classes in the English Education Department. It applied a descriptive qualitative approach, chosen specifically to offer a straightforward description of the phenomenon of the research. Data collection for this study was carried out using observation and interviews. This study involved 13 students as the sample of reticence students. The results revealed nine (9) key factors causing students' reticence in speaking classes. These include anxiety, personality (introverted), lack of confidence, lack of motivation, and low English proficiency. Additionally, fear of negative evaluation, unwillingness to participate, comparison with peers, and uncomfortable classroom atmosphere were identified as significant contributors to students' reluctance to engage in speaking activities. The findings also comprise the strategies to cope with students’ reticence in speaking classes involved classroom arrangements which refers to students’ seating position that makes students participate more and enjoy the class with their peers and using an appropriate teaching method.